Questions of the brothers - Basil, Saint, Bishop of Caesarea, approximately 329-379. (Texts and Studies in Eastern Christianity, 2014)
Basil of Caesarea (c. 328-378) was the great father of Christian monasticism in eastern Anatolia, whose influence spread into all the Greek, Latin and Syriac speaking churches. Basil's counsels for ascetics in community are collected in his Asketikon . The earliest version, the Small Asketikon , did not survive in the Greek, but only in a Latin translation ( The Rule of Basil ), and in a Syriac translation ( The Questions of the Brothers ). Silvas presents the first ever edition of the entire Syriac translation, drawn from five manuscripts, the oldest from the late 5th century. The introductory study shows how the Syriac translator was himself a warm-hearted spiritual father who made his own authorial contributions to the Questions of the Brothers .